INTRAPRENEURSHIP DAN PENGAMBILAN KEPUTUSAN PADA MANAJER TOKO MODERN - Agustini Kurnia; Nicholas Simarmata (Jurnal Psikologi Udayana, 2016)
Tight competition between modern stores is a challenge for organizations of modern store in order to survive and achieve the organization's success. Therefore, the modern store manager is required to make decision as the real action to face that challenge. Decision making is an important process to achieve organization's goals (Luthans, 2006), in which decision-making is done by the manager, because the manager as a key player in the decision-making process (Socea, 2012). Meanwhile, to anticipate a change in the era of globalization and competition, intrapreneurship comes into creativity and an innovative concept that if possessed by modern store manager, it can give an important contribution in the decision making of modern store manager. This research aims to determine whether there is a relationship between intrapreneurship and decision-making of modern store manager. This research is a quantitative method with simple regression analysis. Data is collected through research scales that have been tested for validity and reliability to the 103 modern store managers in the province of Bali, Indonesia. Research data shows normal distribution and linear. The result shows the correlation coefficient is 0.770 and probability at 0.000 (p <0.05). It means that there is a positive and significant relationship between intrapreneurship and decision-making of modern store manager. Contribution of intrapreneurship variable to decision making variable is 59.3%. Key words: intrapreneurship, decision making, manager, modern store